THE USE OF WEBTOON ILLUSTRATION IN IMPROVING THE STUDENTS’ READING ACHIEVEMENT - Gatri Raka Putri karsa; St Asriati AM; Muhammad Arianto Setiadi (English Language Teaching Methodology, 2021)
This research aimed to find out whether the use of Webtoon Media Illustration improve students’ achievement of literal comprehension and interpretative comprehension at the tenth grade students of SMA Negeri 3 Jeneponto. The Subjects of this research consisted of 29 students at the tenth grade MIA 3 of SMA Negeri 3 Jeneponto. The method used quantitave research with pre-experimental research that consisted of pretest, treatment and posttest. Reading test in essay Form was used as an instrument. The result of data indicated that, the students mean score of pre-test in literal comprehension is 56.90. While the post-test was higher 75.52. It meant that there was a significant difference. In addition, the students’ mean score of pre-test in interpretative comprehension was 60.34. While the posttest was higher than mean score of pre-test, the posttest in interpretative comprehension was 79.31. It can be concluded that the use of webtoon media illustration can improve students’ reading achievement